2022
DOI: 10.1183/13993003.01486-2022
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effort during sleep and prevalent hypertension in obstructive sleep apnoea

Abstract: Mechanisms underlying blood pressure changes in obstructive sleep apnoea (OSA) are incompletely understood. Increased respiratory effort (RE) is one of the main features of OSA and is associated with sympathetic overactivity, leading to increased vascular wall stiffness and remodelling. This study investigated associations between a new measure of RE (percentage of sleep time spent with increased RE based on measurement of mandibular jaw movements [MJM]; REMOV, %TST) and prevalent hypertension in adults referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…We have previously reported that RE is also independently associated with prevalent hypertension even in individuals without significant hypoxic burden. 30 , 40 Our data have clinical significance because some future therapeutic decisions for Continuous Positive Airway Press CPAP or alternative primary treatment for OSA will be based on high levels of RE during sleep and not only AHI, especially in individuals with hypertension and/or type 2 diabetes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have previously reported that RE is also independently associated with prevalent hypertension even in individuals without significant hypoxic burden. 30 , 40 Our data have clinical significance because some future therapeutic decisions for Continuous Positive Airway Press CPAP or alternative primary treatment for OSA will be based on high levels of RE during sleep and not only AHI, especially in individuals with hypertension and/or type 2 diabetes.…”
Section: Discussionmentioning
confidence: 92%
“… 7 , 9 , 13 Relatively few studies have evaluated the relevance of other metrics, such as the proportion of sleep time spent with an oxygen saturation below 90%. 8 , 13 Increased RE in individuals with OSA has recently been associated with an increased prevalence of hypertension 30 but has otherwise been poorly studied and is probably underestimated as a risk factor for the cardiovascular and metabolic consequences of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…More recent work by the same group (Le-Dong et al, 2021) demonstrated that machine learning also enabled accurate sleep staging to be performed with an AUC for wake of 0.98, N1/N2 sleep of 0.86, N3 sleep of 0.97, and REM sleep of 0.96. Additionally, mandibular jaw movements (MJM) can be used as a surrogate measure for nocturnal respiratory effort (RE), since the slight protrusions of the mandible during sleep are reflective of respiratory drive (Martinot et al, 2022). Respiratory effort measured via MJM was a stronger predictor of prevalent hypertension than AHI (Martinot et al, 2022).…”
Section: Biological Signalsmentioning
confidence: 99%
“…Additionally, mandibular jaw movements (MJM) can be used as a surrogate measure for nocturnal respiratory effort (RE), since the slight protrusions of the mandible during sleep are reflective of respiratory drive (Martinot et al, 2022). Respiratory effort measured via MJM was a stronger predictor of prevalent hypertension than AHI (Martinot et al, 2022). Such sensors potentially could be embedded within MAS devices to allow capture of compliance data and cardiovascular risk profiling.…”
Section: Biological Signalsmentioning
confidence: 99%
“…Après évaluation de ces 8 articles selon ces critères d'inclusion, 5 articles ont été sélectionnés et 4 articles supplémentaires ont pu être identifiés sur base de leurs bibliographies (figure 1). 11,12 . La dernière étude cherche à évaluer la réponse thérapeutique de l'OAM chez les patients SAHOS afin de guider les praticiens dans la titration de ce dispositif 13 .…”
Section: Le Dispositif Sunriseunclassified